Pengaruh Penerapan Mekanisme Good Corporate Governance Terhadap Praktik Manajemen Laba Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Ambarita, Elfrida; Nuswantara, Dian Anita (AKRUAL: JURNAL AKUNTANSI, 2009)
AbstractThe conflict of interest between agent and principal, asymmetrical information and accounting method selection are able to be used by the manager to do earning management practices. However, it could be reduced by practicing the good corporate governance mechanism which can adjust agent and principalâ€™s interest. The objective of this study is to test the effect of good corporate governance mechanism, as reflected by institutional ownership, managerial ownership, presence of independent board and audit committee existence on the earnings management practice. Using sample from 62 companies in the manufacturing sector at the Jakarta Stock Exchange, which publish financial statement from 2005-2006. This study shows that good corporate governance mechanism insignificantly influence earnings management practice simultaneously. We can infer that mechanism havenâ€™t succeeded to minimize the earnings management practices.Â